Globalization and the politics of development in the Middle East - Henry, Clement M.; Springborg, Robert (The contemporary Middle East, 2010)
Books published in The Contemporary Middle East series address the major political, economic and social debates facing the region today. While the focus of the series is the Middle East and North Africa, books are presented as aspects of the rounded treatment, which cut across disciplinary and geographic boundaries.